The fabrication and characterization of thermoplastic natural rubber (TPNR) nanocomposites reinforced carbon nanotubes (CNTs): the effect of surface treatments on CNTs, mechanical and electrical properties of the nanocomposites / Haida Hazreena Hairuddin - Hairuddin, Haida Hazreena Hairuddin (2013)
Natural rubber/Polyamide 11 (TPNR) nanocomposite were prepared by incorporation of treated and untreated multi-wall carbon nanotubes (MWCNTs) at different loadings (1, 3, 5 and 7 wt.%). TPNR nanocomposites were prepared via melt blending method by using internal mixer at 200°C, 70 rpm mixing speed and 12 minutes processing time for volume ratio 50:10:40 of polyamide 11 (PA), liquid natural rubber (LNR) and natural rubber (NR) respectively. From FTIR patterns, the existing of some other peaks for heat treated and hydrogen peroxide treated MWCNTs were observed. These results show that the heat treatment and hydrogen peroxide treatment lead to the attachment of hydroxyl and carbonyl groups on the surface of MWCNTs. The optimum tensile strength for TPNR reinforced with untreated MWCNTs was achieved at lwt.% nanotubes loading. The highest tensile strength value was about 11.27 MPa that achieved by lwt.% untreated MWCNTs composite compared to TPNR (8.9 MPa). The tensile strength value for TPNR/heat treated MWCNTs composite were much higher for all nano tubes composition compared to untreated MWCNTs composite. The tensile strength for hydrogen peroxide treated MWCNTs nanocomposites is very low even lower than untreated MWCNTs nanocomposites. This trend happened for all the filler compositions. The tensile modulus for TPNR with untreated, heat treated and hydrogen peroxide treated MWCNTs kept on increased until 1 wt.% MWCNTs content only and start to decrease by further addition of nanotubes. The impact strength and elongation at break reduced by increasing filler content for all nanocomposites. The magnitude of conductivity increased with increasing nanotube content. The increasing of nanotubes content will lead to an increase in conductive network among nanofillers as well as the space between the nanotubes, thus, the conductivity of the nanocomposites increased. FESEM image of TPNR with heat treated MWCNTs shows that MWCNTs are well dispersed as compared- to untreated and hydrogen peroxide treated MWCNTs nanocomposites but at higher filler loading (> 7 wt.%), big agglomeration of nanotubes start to occur thus reduced the properties of the composites.